Internet as System and Environment in Cyberspace: Preliminary Ideas from an Ongoing Research - Marcos Palacios (tripleC: Communication, Capitalism & Critique)
The paper discusses the applicability of a pair of concepts - System/Environment - to Internet and Cyberspace. A central point in the discussion is that the pair System/Environment should not be viewed as static analytical poles, but rather as dynamic and interchangeable elements, so that Internet can be conceived both as System and/or Environment, depending on the type of phenomenon one is observing. As a counterpoint to this proposition, the recurrent and “common-sense” notion of Internet as a new medium is presented and criticized. The article also discusses and puts under critical scrutiny the role usually assigned to Internet as a change catalyst or accelerator and the implicit or explicit acceptance of an evolutionary new step in social organization represented by the generalization of New Technologies of Communication. The paper is part of an ongoing research on Digital Cities and Local Networks and proposes some initial steps towards the construction of a model of interpretation based on systems analysis adapted to the particularities of Internet and Cyberspace. The research is anchored on observations of Digital Cities and Local Networks projects at Internet, with special attention to the Aveiro Digital City Project (Portugal).